Co/CoAl/Co trilayer fabrication using spontaneous intermixing of Co and Al: Molecular dynamics simulation - Kim, Sang-Pil; Chung, Yong-Chae; Lee, Seung-Cheol; Lee, Kwang-Ryeol; Kim, Deok-Soo (ELSEVIER SCIENCE SA, 2006)
A multilayer structure was simulated using spontaneous intermixing of Co and Al in epitaxial Co(1 1 (2) over bar 0)/CoAl/Co(1 1 (2) over bar 0) structures. When Al atoms with 0. 1 eV energy were deposited on Co(1 1 (2) over bar 0), an Al(1 0 0) thin film was grown without any intermixing. Interestingly, during subsequent deposition of Co atoms on the grown Al(1 0 0) thin film, an intermixed layer of ordered CoAl structure was spontaneously formed and a highly oriented Co(1 1 (2) over bar 0) crystalline phase was grown above the intermixed region. From the calculations of nearest neighbor distributions, various compositions of CoxAl1-x structures were observed in the mixed region. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: MAGNETIC-PROPERTIES; EPITAXIAL-GROWTH; SANDWICHES; SURFACE; HETEROSTRUCTURES; DEPOSITION; INTERFACE; METALS; FILMS